(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
Wetlands provide the world’s most productive products and services (PAS) for economic purposes. Wetlands are important for fishing, agriculture, biodiversity, and recreational activities. The present paper attempts to estimate the total economic value of the use and nonuse values of the Sone Beel, the largest wetland of Assam. The fishing communities of the Sone Beel area have been associated with the wetland for generations, and they depend on the wetland for their livelihood. We have adopted the market price method, travel cost method, and contingent valuation method for the economic valuation of Sone Beel. The total economic value (TEV) of Sone Beel is estimated as Rs 561,088,074 (USD 6,769,140.46) per annum, with fishing as the main contributor, whose value is estimated at around 84.53 per cent of the TEV of the wetland, followed by duck rearing, water transport, tourism, paddy cultivation, biodiversity conservation, and future use.